Push-off dynamics reveal task-independent alterations in athletes returning to sport after ACL reconstruction - Huby, C. L.; Miari, I.; Hagen, M.; Verschueren, S.; Vanrenterghem, J.; Smeets, A. (Medicine & Science in Sports & Exercise, 2022)
Purpose Athletes with an anterior cruciate ligament (ACL) reconstruction (ACLR) show persisting biomechanical and neuromuscular landing alterations. So far, most research focused on the landing phase of dynamic tasks where most ACL injuries occur. This study will assess whether these landing alterations are also present in the propulsion phase, in an attempt to identify generalized movement alterations.